Single Mutation in Shine-Dalgarno-Like Sequence Present in the Amino Terminal of Lactate Dehydrogenase of Plasmodium Effects the Production of an Eukaryotic Protein Expressed in a Prokaryotic System - Cicek, Mustafa; Mutlu, Ozal; Erdemir, Aysegul; Ozkan, Ebru; Saricay, Yunus; Turgut-Balik, Dilek (HUMANA PRESS INC, 2013)
One of the most important step in structure-based drug design studies is obtaining the protein in active form after cloning the target gene. In one of our previous study, it was determined that an internal Shine-Dalgarno-like sequence present just before the third methionine at N-terminus of wild type lactate dehydrogenase enzyme of Plasmodium falciparum prevent the translation of full length protein. Inspection of the same region in P. vivax LDH, which was overproduced as an active enzyme, indicated that the codon preference in the same region was slightly different than the codon preference of wild type PfLDH. In this study, 5'-GGAGGC-3' sequence of P. vivax that codes for two glycine residues just before the third methionine was exchanged to 5'-GGAGGA-3', by mimicking P. falciparum LDH, to prove the possible effects of having an internal SD-like sequence when expressing an eukaryotic protein in a prokaryotic system. Exchange was made by site-directed mutagenesis. Results indicated that having two glycine residues with an internal SD-like sequence (GGAGGA) just before the third methionine abolishes the enzyme activity due to the preference of the prokaryotic system used for the expression. This study emphasizes the awareness of use of a prokaryotic system to overproduce an eukaryotic protein.
Keywords: Shine-Dalgarno sequence; Site-directed mutagenesis; Lactate dehydrogenase; Plasmodium; HUMAN MALARIA PARASITE; MESSENGER-RNA; RECOMBINANT PROTEINS; ESCHERICHIA-COLI; RIBOSOMAL-RNA; Q-BETA; FALCIPARUM; GENOME; GENE; SITE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology